Antimicrobial and antimalarial activity of Tabernaemontana elegans Stapf. (Apocynaceae) - Bapela, Mahwahwatse Johanna (University of Pretoria, 2024)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2019.